Influence of supplemental maslinic acid (olive-derived triterpene) on the post-mortem muscle properties and quality traits of gilthead seabream - Matos, Elisabete (2014)
Maslinic acid, a natural triterpene, was evaluated as a dietary supplement to modulate glycogen post-mortem mobilization in gilthead seabream muscle. For this purpose, a multidisciplinary trial was undertaken, where flesh quality criteria, as well as biochemical and histological parameters, enzymatic activities and protein expression in the muscle were assessed. Supplementing gilthead seabream diets with maslinic acid mainly resulted in hypertrophy of muscle fibres and inhibition of cathepsin B activity, with no observed differences in terms of glycogen and ATP content of the muscle, as well as glycogen phosphorylase activity. Proteomic analysis showed a low impact of maslinic acid supplementation on muscle metabolism, with most changes reflecting increased stress coping capacity and muscle hypertrophy in maslinic acid-fed fish. As a finishing strategy to improve the muscle's energetic status, the usefulness of maslinic acid seems limited. However, it shows potential for promoting muscle growth in this species.